Exploring Family Perceived Social Support in Shaping and Sustaining Academic Achievement among High-Achieving Students: A Phenomenological Study - Bentar Putra Anggara; Ira Darmawati (Al-Qalam Institue, 2026)
This study aims to explore in depth how students perceive family social support in shaping and sustaining their academic achievement. Employing a qualitative approach with a phenomenological design, the study involved five high-achieving senior high school students selected through purposive sampling. Data were collected through in-depth interviews conducted twice with each participant, supported by observation and documentation, and analyzed using phenomenological analysis, including data reduction, identification of significant statements, thematic clustering, and synthesis of essential meanings. The findings reveal that family social support is perceived as a critical psychological experience that contributes to the maintenance of academic achievement. Four major themes emerged: emotional support as a source of psychological safety, appraisal support as reinforcement of academic self-confidence, informational support as adaptive guidance fostering self-regulation, and instrumental support as a symbol of family commitment to education. These findings imply that family support functions as a protective and facilitative system that not only enhances students’ academic performance but also sustains their motivation and psychological well-being.